Novel Role of Protein Kinase C Delta Tyr(311) Phosphorylation in Vascular Smooth Muscle Cell Hypertrophy by Angiotensin II - Nakashima, Hidekatsu (2008)
We have previously shown that activation of protein kinase C δ (PKCδ) is required for angiotensin II (AngII)-induced migration of vascular smooth muscle cells (VSMCs). Here, we have hypothesized that PKCδ phosphorylation at Tyr(311) plays a critical role in VSMC hypertrophy induced by AngII. Immunoblotting was used to monitor PKCδ phosphorylation at Tyr(311), and cell size and protein measurements were used to detect hypertrophy in VSMCs. PKCδ was rapidly (0.5–10 min) phosphorylated at Tyr(311) by AngII. This phosphorylation was markedly blocked by a Src family kinase inhibitor and dominant-negative Src, but not by an epidermal growth factor receptor kinase inhibitor. AngII-induced Akt phosphorylation and hypertrophic responses were significantly enhanced in VSMCs expressing PKCδ wild type compared with VSMCs expressing control vector, whereas the enhancements were markedly diminished in VSMCs expressing PKCδ Y311F mutant. Also, these responses were significantly inhibited in VSMCs expressing kinase-inactive PKCδ K376A compared with VSMCs expressing control vector. From these data, we conclude that not only PKCδ kinase activation but also the Src-dependent Tyr(311) phosphorylation contributes to Akt activation and subsequent VSMC hypertrophy induced by AngII, thus signifying a novel molecular mechanism for enhancement of cardiovascular diseases induced by AngII.